العطف بين اللغة العربية واللغة الإندونيسية (دراسة تحليلية تقابلية) - Noor Zinatul Hamidah; Zahrul Fata (Pascasarjana IAIN Ponorogo, 2024)
Every language has similarities and differences. Similarities and differences in language are studied in a science called contrastive analysis of language. Contrastive analysis aims to identify similarities and differences between two or more languages. One of the similarities and differences in language is in terms of rules. This study aims to analyze the similarities and differences of 'athof between Arabic and Indonesian because 'athof in Arabic has certain characteristics which are also found in Indonesian conjunctions. In addition, some students made mistakes in composing sentences related to 'athof. Most students are still influenced by the rules of conjunction in Indonesian. This research uses the type of library research. The approach in this study is a descriptive qualitative approach. The results showed that there were some similarities and differences between 'athof in Arabic and Indonesian. Among the similarities between Arabic and Indonesian are atof in terms of understanding and use. The difference lies in the type and some uses of conjunctions that are not found in the Arabic 'athof.